Strategi Kepala Sekolah dalam Upaya Meningkatkan Kinerja Guru pada Masa Pandemi Covid-19 di UPT SDN 2 Majannang Kec. Balocci Kab. Pangkajene dan Kepulauan - Rahman Kambi; Radiatan Mardiah; Fitri Rezki Amaliah; Putra Ananda Pratama Ali (Institut Nalanda, 2023)
This thesis aims to reveal how the principal's strategy is in an effort to improve teacher performance at UPT SDN 2 Majannang Kec. Balocci Kab. Pangkajene and Islands, which is broken down into the main sub-problems, namely What is the Strategy of the Head of UPT SDN 2 Majannang in an effort to improve teacher performance during the Covid-19 pandemic? To answer the problem raised, a qualitative research was carried out using a phenomenological and sociological approach by taking data sources from the UPT SDN 2 Majannang Principal and several UPT SDN 2 Majannang teachers. Research data was taken through observations and interviews obtained during the research carried out, with the presence of researchers in the field and equipped with interview guideline text along with stationery and smartphones as research instruments, then the process of data reduction and verification was carried out using data triangulation techniques. Furthermore, the data is processed and analyzed and then draw conclusions based on the results of the research conducted.